PENERAPAN MODEL PEMBELAJARAN MASTERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS V SD NEGERI 017 BAGAN LIMAU KECAMATAN UKUI - Edi Mohamad Muhtar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The low learning outcomes in Civics among fifth-grade students of SD Negeri 017 Bagan Limau formed the background of this study. This research aimed to improve Civics learning outcomes through the implementation of a mastery learning model. The study employed classroom action research conducted in two cycles. The data used were students’ Civics learning outcome scores. The results revealed a significant improvement in learning outcomes. This improvement was evidenced by: (a) preliminary data showing that only 50% of students achieved mastery, which increased to 76% in the first cycle and reached 90% class mastery in the second cycle; and (b) an increase in the average student score from a baseline of 65 to 68.25 in the first cycle, and further to 74.5 in the second cycle. Therefore, it can be concluded that the mastery learning model effectively improves Civics learning outcomes for fifth-grade students of SD Negeri 017 Bagan Limau.